คุณลักษณะอันพึงประสงค์ของผู้บริหารสถานศึกษายุคประเทศไทย 4.0 สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาบุรีรัมย์ - Khankhammuen, Sarawut (วารสารวิจัยและนวัตกรรมท้องถิ่น, 2023)
The purposes of this research are to study and compare opinions of teachers on the Desired Characteristics of School Administrators in Thailand 4.0 under Buriram Secondary Educational Service Area Office. Classified by educational level, work experience and academic standing. The sampling was obtained by stratified sampling and the sampling was determined according to Cohen table of 283 subjects. The research instrument was questionnaires checking the validity of IOC between 0.8-1.0, Cronbach's alpha coefficient was 0.970. The statistics used in the research were frequency, percentage, mean, standard deviation, t-test and One-way ANOVA analysis of variance was found, when differences were found, a pair of tests was performed according to the Scheffé method (Scheffé's post hoc comparison). The research results were found that (1) Teachers have an opinion on the Desired Characteristics of School Administrators in Thailand 4.0 under Buriram Secondary Educational Service Area Office, the overall and each aspect are in a high level. (2) Teachers with the different educational levels, work experience and academic standing have the same opinions on the Desired Characteristics of School Administrators in Thailand 4.0 under Buriram Secondary Educational Service Area Office, Overall found no difference. when considering each aspect, Teachers with different academic backgrounds have opinions on Knowledge-ability, Personality and Human relations The difference was statistically significant at the .05 level.